Basal ganglia dysfunction in complex regional pain syndrome – A valid hypothesis?. (2nd November 2016) - Azqueta‐Gavaldon, M.; Schulte‐Göcking, H.; Storz, C.; Azad, S.; Reiners, A.; Borsook, D.; Becerra, L.; Kraft, E.
Abstract: Complex regional pain syndrome (CRPS) is a poorly understood pain disorder of the limbs. Maladaptive cortical plasticity has been shown to play a major role in its pathophysiological presentation. Recently, there is increasing interest in the role of the basal ganglia (BG), since clinical findings and neuroimaging studies point to possible BG involvement in CRPS. CRPS symptoms are often characterized by movement disorders associated with BG dysfunction. Very frequently, dystonia and tremor are reported and, to a lesser extent, myoclonus. Neuroimaging studies present inconsistent findings concerning altered brain networks and mainly focus on cortical areas. Subcortical contribution to this disorder has so far been neglected. Clinical data presenting BG dysfunction‐related movement disorders in CRPS patients raise the hypothesis of BG dysfunction in this syndrome. Moreover, several neuroimaging studies documented abnormalities in the BG and in the frontal, parietal and limbic cortical areas. These regions are functionally and anatomically connected in motor, pain and working memory networks. Put together, these findings call for further characterization of the dynamic cortical and subcortical interactions in CRPS. Significance: This paper presents an overview of our current knowledge about BG pathology in CRPS. A better understanding of the involvement of the BG in the CRPS pathology holds the potential for developing and improving efficacious, mechanism‐based treatment modalities.